Pola Aktivitas Harian dan Interaksi Banteng dan Rusa dalam Pemanfaatan Kawasan Padang Rumput Sadengan di Taman Nasional Alas Purwo, Banyuwangi, Jawa Timur - Subeno Subeno (Fakultas Kehutanan Universitas Gadjah Mada, 2007)
Daily Activities Pattern and InteractionBetween Banteng and Deerin Sadengan Grazing a Area in Alas Purwo National Park, Banyuwangi, East JavaThis research was aimed to compare the pattern of daily activities between banteng and deer, and their interaction on using feeding ground in Alas Purwo National Park, Banyuwangi, East Java. Methods used in this research were scan sampling, focused on groups of banteng and deer and focal animal sampling for four chosen individuals from each group. The observations began at 06.00 until 18.00. Daily activities recorded were resting, moving, feeding and drinking. Data analysis was done through arrangement of an ethogram to show daily activity and the time budget, and descriptive analysis to portray daily activity and interaction between banteng and deer. The results show that there are differences in the time used for resting and feeding between banteng and deer. Banteng used feeding ground more for resting (93,2%) and moving (5,7%). While deer used more for feeding (36,6%) and resting (61,8% ). Among chosen individuals of banteng and deer time variation in daily activities was apparent. Adult female of banteng has the highest time for resting (10,6 hours). It also occurred in adult female of deer (8,4 hours). Individual of deer which has the highest time for feeding is offspring with duration of 6,1 hours. Interaction between banteng and deer on using feeding ground tended toward symbiosis of commensalisms, in which they use it together without fighting. They too will vocalize together whenever other species wants to use the feeding ground.